The Effect Of Movement Stories On Learning Floor Exercises In Artistic Gymnastics for Children With Learning Disabilities Aged 7 Years Old - Ibrahim, Ismael; Aladdin, Mais; Nazar, Tariq (Journal of Physical Education, 2018)
The Effect Of Movement Stories On Learning Floor Exercises In Artistic Gymnastics for Children With Learning Disabilities Aged 7 Years OldThe importance of the research lies in using movement stories to teach gymnastics skill for children with learning disabilities. The problem of the research lies in the lack of movement stories use in physical education class and on children with learning disabilities aged 7 years old. The researchers used the experimental method. The subjects were (20) child who suffer from learning disabilities in Al Nebras School. The main experiment consisted of 24 training session with two units per week. The researcher concluded that the experimental group surpassed the controlling group in learning floor exercises in gymnastics. Finally the researcher recommended using movement stories in learning artistic gymnastics and other sports.